Long-term soccer-specific training enhances the rate of physical development of academy soccer players independent of maturation status - Wrigley, R. D.; Drust, B.; Stratton, G.; Atkinson, G.; Gregson, W. (International Journal of Sports Medicine, 2014)
The aim of the study was to compare 3-year changes in physical performance between junior soccer players selected for an elite academy and age-matched controls. The 3-year changes in indicators of the physical performance were quantified in 12-16-year-old Premier League Academy (n=27) and non-academy soccer players (n=18). Data were analysed with an age-group×competitive level general linear model, covariate-adjusted for initial performance level and change in maturation. Covariate adjusted mean±SD changes were greater (standardised effect size>0.7) for the academy players in terms of countermovement jump (7.3±2.6 vs. 5.4±2.5 cm), 10 m sprint (- 0.15±0.05 vs. - 0.10±0.04 s), 20 m sprint (- 0.30±0.16 s vs. - 0.15±0.13 s), agility (- 0.19±0.01 s vs. - 0.08±0.08 s), repeated sprint (- 0.60±0.26 s vs. - 0.41±2.1 s) and intermittent endurance capacity (1 128±406 vs. 315±370 m). These data indicate that a 3-year programme of training in an elite soccer academy is associated with greater changes in physical performance indicators independently from the initial performance level of the child and change in maturation over the same period of time.